Formulation and Evaluation of Rosiglitazone Mouth Dissolving Tablet - G ARJUN; M.SRAVAN PRASAD; D SANTHOSHA; G.ACHAIAH (International Journal of Pharma and Bio Sciences, 2010)
To improve patient compliance, mouth dissolving tablets have emerged as an alternative to conventional dosage forms. Rosiglitazone and Sulfonylurea are given in combination for treatment of type 2 Diabetes Mellitus for long term therapy. During this therapy, it is observed that there is uncontrolled increase of blood glucose level. Therefore, mouth dissolving tablets of Rosiglitazone were prepared to overcome this unusual problem and to make use of the inherent advantages of the novel drug delivery system. Rosiglitazone with Sodium Starch Glycolate, Cross povidone & Cross carmellose sodium were tableted with a view to obtain mouth dissolving tablets. Rosiglitazone mouth dissolving tablets containing Cross povidone & Cross carmellose sodium in the ratio 1:1 showed maximum drug release. Formulations were subjected to stability studies. Formulations are stable for 4 weeks at 40 oC / 75 % RH with insignificant change in the hardness, disintegration time and in vitro drug release pattern.